A Revisit Intention Wana Wisata Sumber Biru: A Review of Content Marketing and Customer Experience - Fahimah, Mar'atul; Rizal Zulmi, Mohammad (Universitas Indo Global Mandiri Palembang, 2025)
Objective: The aim of this study is examine how content marketing and customer experience, both separately and together, revisit intention Design/Methods/Approach: The method used in this research is a quatitative approach. The research population consists of tourists who access the Instagram content of Sumber Biru tourist destination and those who have visited the destination. A total of 100 respondents were chosen through purposive sampling. The data was then analyzed using methods suitable for the study's objectives, this study uses Multiple Linear Regression Analysis. Findings: Content marketing has a strong and meaningful impact on revisit intention. Likewise with customer experience, which is proven to have a positive and significant impact on the desire of tourists to return to visit the destination.. Originality/Value: This research explores the connection between content marketing and customer experience on visitors' intention to return to Sumber Biru Tourism Park. In this study, the authors analyze the various factors that influence customer experience and how content marketing can increase visitors' desire to return. This research is useful for marketing professionals, destination managers, and researchers interested in the effect of digital marketing strategies on visitor behavior. The authors focused on developing a thorough research method with a quantitative approach to measure the relationship and provide new insights into the influence of content marketing and customer experience in the tourism industry. Practical/Policy implication: This study focuses on visitors to Sumber Biru Tourism Park, offering insights for managers to optimize content marketing and enhance customer experiences to boost return visits. Future research could explore other destinations and include variables like visitor demographics or promotion types to deepen understanding of factors influencing revisit intention.